Effectiveness of telenutrition in a women's weight loss program - Kuzmar, Isaac E; Cortés-Castell, Ernesto; Rizo, Mercedes (PeerJ PrePrints, 2014)
Objective: To evaluate the effectiveness of telenutrition versus traditional nutritional consultation for obese patients. Methods: A comparative clinical study was conducted among 233 (including 20 dropouts and 60 failures) obese or overweight women who consulted a nutrition clinic in Barranquilla (Colombia) for nutritional assessment by telenutrition or traditional attention that includes a weekly follow-up consultation over 16 weeks, food consumption patterns, Body Mass Index (BMI, kg/m2) register, waist and hip circumference register. Treatment response and difference between telenutrition and traditional consultation were made according to BMI, waist, hip and initial-waist/height ratio. Data´s nonparametric statistical comparison was made. Results: In 68 (29.2%) women who chose traditional attention, 9 (37.5%) dropped out, 24 (40%) failed and 35 (23.5%) were successful, showing 1.4%(1.0 SD) BMI loss, 5.8% (3.4 SD) in waist circumference, 4.5% (2.8 SD) in hip circumference and 0.04% (0.02 SD) in iwaist/height ratio. In 165 (70.8%) women who chose telenutrition, 15 (62.5%) dropped out, 36 (60%) failed and 114 (76.5%) were successful, showing 1.1% (1.0 SD) BMI loss, 5.0% (3.2 SD) in waist circumference, 3.5% (3.1 SD) in hip circumference and 0.03% (0.02 SD) in iwaist/height ratio. A significance level of p<0.05 is considered. Conclusion: Telenutrition has a failure or dropout risk factor about half values of traditional consultation with slightly statistically significant differences. This study concludes that telenutrition can support or sometimes replace the traditional consultation when developing weight loss programs in obese women.
Keywords: telenutrition; e-health; obesity; overweight